Assessment of Research Collaborations for Improving Intellectual and Economic Performance in Public Renewable Energy R&D - Kim, Dohyoung; Jang, Sojin; Jung, Sungdo; Hwang, Junseok (School of Business and Management Institut Teknologi Bandung, 2021)
Abstract. Public R&D investment in renewable energy has burgeoned at the global level in a concerted effort to expedite energy transition. Unlike traditional energy sources, the renewable energy industry produces a favorable collaboration environment for small and medium enterprises, affecting traits of R&D collaboration in R&D as well. The main purpose of this study is to find relationships between R&D collaboration and intellectual & economic performances in renewable energy R&D. We have analyzed 484 projects completed between 2006 and 2014 in South Korea’s public renewable energy R&D program. We found that university-industry-government research institute collaboration is not the most effective for creating intellectual nor economic performance, interpreting as a necessity in the revision on current UIG collaboration policy. For a leader organization, we found that medium enterprises are the most positively related with economic outcomes, interpreting medium enterprises had as much technical competency and investment capacity as large enterprises. Keywords: R&D, performance measurement, collaboration, renewable energy, triple helix, r&d leader